Pengaruh Spasi Pada Performa Prefabricated Vertical Drain (PVD) Dalam Perbaikan Tanah Lunak - Hayatul Hamida; Syawal Satibi; Muhardi Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Soil condition heaps of times be a problem in a construction work, it is cause the condition soft soil layer have low permeability. Soft ground improvement with vertical drain is complex analysis for consolidation, got in on space of prefabricated vertical drain (PVD). Space is influential at times of settlement. If space too small then it’s not economical, because it will more point to installation PVD. So, did analysis comparison Chai et al method and average method. This comparison between the two method give the result is not to be different, so installation PVD should be with space 1,5 m. it’s from the result with soil data of PLTU Riau. Keywords: Ground Improvement, penetrated vertical drain, degree of consolidation (U)